THERMAL COMFORT EFFECTS ON PHYSIOLOGICAL ADAPTATIONS AND GROWTH PERFORMANCE OF WEST AFRICAN DWARF GOATS RAISED IN NIGERIA - Popoola, M.A.; Bolarinwa, M.O; Yahaya, M.O.; Adebisi, G.L.; Saka, A.A. (European Scientific Journal, ESJ, 2014)
Physiological traits and growth performance of West African dwarf (WAD ) goats raised under hot-humid conditions were assessed, 12 growing WAD goats managed intensively were used for the study. Temperature and relative humidity of the farm were monitored across seasons (rain and dry) using thermo-hygrometer, the study was conducted during rainy and dry seasons to compare parameters in normal and heat stress conditions. Months of December, 2012 to February, 2013 were considered as the dry season, while the months of March, 2013 to May, 2013 were considered as the rainy season. Data obtained for temperature and relative humidity were used to develop an index for measuring thermal comfort level for the goats. Data were collected on growth performance and physiological characteristics of the goats. Rectal temperature and respiration rate were significantly affected (P<0.001) by temperature humidity index (THI). However, pulse rate was the only physiological trait of the goats that was not significantly affected (P>0.001) by THI. Also, the body weight and average daily gain of the goats significantly differed with increase in the THI. Rising ambient temperature and relative humidity as expressed in form of THI are associated with poor growth performance as well as adverse effects on physiological characteristics of the animals.